Report of the Study Team on Tribal Development Programmes Assam - Planning Commission (Planning Commission, 1966)
The State of Assam is situated in the north-east corner of India between 21°40' and 28°41' - north, latitude and 89°30' and 90°15' - east longitude. It is bounded on the north and north-east by Bhutan and NEFA, on the east by Nagaland and Manipur, on the south and south east by Burma and on the west by Tripura, East Pakistan and West Bengal. A narrow strip of land, lying in the sub mountainous regions of the Himalayas, connects it with the rest of India.
Committee on Plan Projects, Planning Commission